Promoting fruit and vegetable consumption among school children through nutrition intervention programme. - Seethal K C (Department of Home Science, College of Agriculture, 2011)
The over arching goals of this study was to promote the fruit and vegetable consumption among school children through nutrition intervention programme. Recent literature shows that the consumption of fruits and vegetables among school children are inadequate and the trend of junk food eating habit is increasing alarmingly. A wealth of anecdotal evidence reveals that nutrition intervention programmes with gardening effect multiple domains in the lives of the subjects.